A study on noise level for school at SJRC Samtet Ipoh and Pusat Tingkatan Enam Seri Ipoh / Mohd Amirul Afiq Md Norzeri and Nazhatul Jamaludin - Md Norzeri, Mohd Amirul Afiq; Jamaludin, Nazhatul (2018)
Noise pollution around the educational area can negatively affect the performance of both teachers and students. The noise level should be around the range of 35 dBA in the school area. Little attention has been given by individuals or government concerning noise pollution in schools` surrounding. A study of this problem is presented in this paper by doing some measurement of the noise level at the school located near city at SJRC Samtet Ipoh and Pusat Tingkatan Enam Seri Ipoh has been conducted to measure noise level in its surrounding. The result of this study shows that the rate of noise level in SJRC Samtet Ipoh is high and not suitable for the school's environment.